Representasi Matematis Siswa dalam Menyelesaikan Masalah Teorema Pythagoras berdasarkan Tahapan Polya Ditinjau dari Perbedaan Gender - Dinda Putri Lestari; Evangelista Lus Windyana Palupi (Program Studi S1 Matematika UNESA, 2023)
Mathematical representations is the real product or result that represent mathematical ideas in various forms, such as diagrams, graphs and other concrete forms to help finding solutions to problems. Mathematical representation in problem solving is the main thing since, the use of right mathematical representation can help in solving the problem correctly. The purpose of this research is to describe the mathematical representation of masculine male students and feminine female students in solving Pythagorean Theorem problems based on Polya's stages. The research method used is descriptive qualitative. The research subjects were 3 masculine male students and 3 feminine female students at Junior High School 2 Gresik. Data is collected using BSRI questionnaire, mathematical ability test, problem solving test, and interviews. The results of problem solving test were showed that at the stage of understanding the problem, masculine male students presented known information using visual and symbolic representations while feminine female students used verbal and symbolic representations. To present what is being asked, masculine male students and feminine female students using verbal representations. At the planning stage, masculine male students and feminine female students explained solving strategies using verbal representations. At the stage of carrying out the plan, masculine male students and feminine female students solving the problems using visual, symbolic, and verbal representations, and presenting the results of the solution using verbal representations. At the re-examining stage, masculine male students and feminine female students using verbal representations to conclude the completion results and checking the completion results using symbolic representations.